Effect of High Temperature in Concrete for Different Mineral Additives and Rates - Esen, Yuksel; Kurt, Alper (Korean Society of Civil Engineers-Ksce, 2018)
In this study, the change of the effect of high temperature in concrete by the types of mineral additives was examined experimentally. For this purpose, CEM I 42,5 R cement was used together with different minerals such as Barite, Diatomite, Silica fume, F class Fly ash that are added in a substituted manner at the rates of 10%, 20%, 30% and 40% by volume. Dry unit weights, underwater weights and water saturated weights of these concrete samples with mineral additives with 28-day strength were found. Ultrasonic Pulse Velocity (UPV) measurements of the concrete samples, the water absorption percentages by weight of which were determined, were performed. The samples which were then exposed to high temperatures such as 200, 400, 600 and 800A degrees C were left for cooling at room temperature, and then, their compressive strength was measured. While the highest water absorption rates were in Diatomite reinforced concrete, the highest compressive strengths were obtained in Silica fume reinforced concrete.
Keywords: high temperature; concrete; barite; diatomite; silica fume; Fly ash